Thermal fatigue reliability for Cu-Pillar bump interconnection in flip chip on module and underfill effects. Issue 1 (2nd February 2015) - Kwak, Jae B.; Chung, Soonwan
Abstract : Purpose: – The purpose of this paper is to assess the thermo-mechanical reliability of a solder bump with different underfills, with the evaluation of different underfill materials. As there is more demand in higher input/output, smaller package size and lower cost, a flip chip mounted at the module level of a board is considered. However, bonding large chips (die) to organic module means a larger differential thermal expansion mismatch between the module and the chip. To reduce the thermal stresses and strains at solder joints, a polymer underfill is added to fill the cavity between the chip and the module. This procedure has typically, at least, resulted in an increase of the thermal fatigue life by a factor of ten, as compared to the non-underfilled case. Yet, this particular case is to deal with a flip chip mounted on both sides of a printed circuit board (PCB) module symmetrically (solder bump interconnection with Cu-Pillar). Note that Cu-Pillar bumping is known to possess good electrical properties and better electromigration performance. The drawback is that the Cu-Pillar bump can introduce high stress due to the higher stiffness of Cu compared to the solder material. Design/methodology/approach: – As a reliability assessment, thermal cyclic loading condition was considered in this case. Thermal life prediction was conducted by using finite element analysis (FEA) and modified Darveaux's model, considering microsize of the solder bump. In addition, thermo-mechanical properties of four different underfill materials were characterized, such as Young's modulus at various temperatures, coefficient of temperature expansion and glass transition temperature. By implementing these properties into FEA, life prediction was accurately achieved and verified with experimental results. Findings: – The modified life prediction method was successfully adopted for the case of Cu-Pillar bump interconnection in flip chip on the module package. Using this method, four different underfill materials were evaluated in terms of material property and affection to the fatigue life. Both predicted life and experimental results are obtained. Originality/value: – This study introduces the technique to accurately predict thermal fatigue life for such a small scale of solder interconnection in a newly designed flip chip package. In addition, a guideline of underfill material selection was established by understanding its affection to thermo-mechanical reliability of this particular flip chip package structure.